Integrated molecular characterization of IDH-mutant glioblastomas - Korshunov, Andrey; Casalini, Belén; Chavez, Lukas; Hielscher, Thomas; Sill, Martin; Schrimpf, Daniel; Stichel, Damian; Capper, David; Sturm, Dominik; Lichter, Peter; Herold-Mende, Christel; Wick, Wolfgang; et al. (Neuropathology & applied neurobiology, 2019)
Aims: Mutations of isocitrate dehydrogenase (IDH)1/2 affect almost all astrocytomas of WHO grade II and III. A subset of IDH-mutant astrocytic tumours progresses to IDH-mutant glioblastoma or presents with the histology of a glioblastoma at first presentation. We set out here to assess the molecular spectrum of IDH-mutant glioblastomas. Methods: We performed an integrated molecular analysis of a mono-centric cohort (n = 97); assessed through genome-wide DNA methylation analysis, copy-number profiling and targeted next generation sequencing using a neurooncology-tailored gene panel. Results: Of these 97 IDH-mutant glioblastomas, 68 had a glioblastoma at first presentation (‘de novo’ IDH-mutant glioblastoma) and 29 emerged from a prior low-grade lesion (‘evolved’ IDH-mutant glioblastoma). Unsupervised hierarchical clustering of DNA methylation data disclosed that IDH-mutant glioblastoma (‘de novo’ and ‘evolved’) formed a distinct group separate from other diffuse glioma subtypes. Homozygous deletions of CDKN2A/B were found to be associated with shorter survival. Conclusions: This study demonstrates DNA methylation patterns in IDH-mutant glioblastoma to be distinct from lower-grade astrocytic counterparts but homogeneous within de novo and evolved IDH-mutant glioblastomas, and identifies CDKN2A as a marker for possible genetic sub-stratification.
First published: 16 October 2018
Gesehen am 18.09.2019